Rediscovery of Cnemaspis nilagirica Manamendra-Arachchi, Batuwita and Pethiyagoda, 2007 (Squamata: Gekkonidae) from Kerala, India with notes on morphology and distribution - Cyriac, Vivek Philip; Johny, Alex; Umesh, Pavukandy; Palot, Muhamed Jafer; Campbell, Patrick D (Zootaxa, 2019)
Cnemaspis nilagirica was described by Manamendra-Arachchi, Batuwita and Pethiyagoda in 2007 based on a single female specimen that was a syntype of Gonatodes kandianus var. tropidogaster described by Boulenger in 1885. However, a living population of this species has not been reported since its original description by Boulenger. Based on fresh material and comparisons with the holotype of C. nilagirica, we here report the collection of this species after over 130 years. We provide the first description of a male specimen and additional information on morphological variation, distribution and natural history.